TECHNOLOGIES AND PROCESSING OF OIL SHALE DEPOSITS OF UZBEKISTAN (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
The object of the study is oil shale and host rocks of the Sangruntau deposit and oil shale of the Baysun deposit. During the work, thermal decomposition of the sample material was carried out using a two-stage scheme on geological samples collected from the experimental block of the Sangruntau deposit. At the first stage, pyrolysis (burning without oxygen access) was carried out, and at the second stage, oxidative burning. Based on the results of thermal analysis, the yield of liquid and gas phases of pyrolysis, semi-coke and semi-coke ash from oil shale, overlying and underlying rocks was determined. It is shown that the main criterion for determining the boundaries of the shale formation is the yield of shale oil, and not the color of the rock. A pattern of increasing concentrations of many metals (vanadium, molybdenum, REE) with an increase in the yield of shale resin for rubidium and cesium is the opposite. The 20 most promising elements for extraction have been identified.